Polydipsia, hyponatremia and rhabdomyolysis in schizophrenia: A case report - Chen, Li-Chi (World J Psychiatry, 2014)
The prevalence of polydipsia among patients with schizophrenia is 6%-20%. Around 10%-20% of patients with polydipsia may develop hyponatremia and even complicated with rhabdomyolysis. Here we presented a 40-year-old man with schizophrenia, who had received paliperidone 15 mg/d for more than one year, and polydipsia was noted. In Jan, 2014, he developed hyponatremia (Na 113 mEq/L) with consciousness disturbance. After 3% NaCl (500 cc/d) intravenous supplement for three days, the hyponatremia was corrected, but rhabdomyolysis developed with a substantial elevation in the level of creatine kinase (CK) to 30505 U/L. After hydration, the CK level gradually decreased to 212 U/L. Both the hyponatremia itself and quick supplementation of NaCl can cause rhabdomyolysis. If rhabdomyolysis is not recognized, insufficient hydration or water restriction for polydipsia may further exacerbate the rhabdomyolysis with a lethal risk. In this case, we highlight the possible complication of rhabdomyolysis with polydipsia-induced hyponatremia. In addition to monitoring the serum sodium level, the monitoring of CK is also important; and switching of antipsychotic may improve the polydipsia.